Status Kewarganegaraan Bagi Anak (Intended Parents Embryo) Warga Negara Indonesia Menggunakan Mekanisme Gestational Surrogacy - Adi, Abdulloh; Syaiful Aris (Jurist-Diction, 2025)
Assistive Reproductive Technology (ART) is contained in Article 58 of Law Number 17 of 2023 concerning Health which only recognizes the IVF process, and implicitly prohibiting about Gestational Surrogacy and impact on sitizenship status without paying attention to the principle of legality. The aim of this research is to determine the impact of differences in Gestational Surrogacy procedure arrangements on citizenship status, especially for granting Indonesian citizenship from thet procedure. This writing method is normative legal research using a conceptual approach and a statutory regulatory approach. The result of this research is that there is a causal impact of differences in the settings of Gestational Surrogacy procedures with citizenship status, where in several countries children resulting from Gestational Surrogacy have stateless status. In Indonesia itself, children resulting from this procedure still have Indonesian citizenship status. However, it must be the status of an illegitimate child